Application du concept de responsabilisation personnelle aux usages sociaux des technologies d’information et de communication en santé - Marc LEMIRE (Tic & Société)
It has been suggested that the use of information and communication technologies (ICT) represents one of the ways that the public can become more actively involved and assume more responsibility in their health care. To better understand the logics underlying this will toward transformation, we suggest applying the concept of personal empowerment to the analysis of the social uses of ICT. This paper presents a synthesis of recent analyses and case studies and discusses the various logics of empowerment and their respective implications in terms of approaches to health care. To this end, a matrix has been developed of the four interpretative paradigms associated with this concept. While confirming the coexistence of four distinct logics, the results also reveal two dominant trends: an intensification of the control and standardization processes resulting from the authority relationships typically found in health, and an intensification of the ensuing autonomization and self-assertion processes, either through market or social relationships. In fact, such an approach may lead to a critical understanding of ICT as an instrument for governance or as devices that may help breathe new life into the power relationships between health stakeholders.